2021
DOI: 10.1111/joss.12723
|View full text |Cite
|
Sign up to set email alerts
|

Analytic versus holistic: Cognitive styles can influence consumer response and behavior toward foods

Abstract: While there is a growing body of attention to the diversity of cognitive styles among individuals, that has yet to be directly applied to sensory and consumer sciences. This study was aimed at identifying how divergent analytic and holistic cognitive styles can affect individuals' food-related experiences. Participants were classified into either analytic or holistic cognitive style groups based on their scores on the Analysis-Holism Scale. Focus group interviews were conducted to identify group differences wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
36
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(45 citation statements)
references
References 70 publications
7
36
2
Order By: Relevance
“…Across the conducted analyses and corresponding results, the consistent finding was a superior performance of the F-AHS, relative to the prior AHS findings from Beekman and Seo (2023; see also Beekman, 2022). This main finding was shown through results from the F-AHS segmentation resulting in greater AH response differences that more closely matched with prior AH literature compared to Beekman and Seo's findings that relied on AHS segmentation (Beekman & Seo, 2023; see also Beekman, 2022) findings that relied on AHS segmentation. When first looking solely at the mean rating differences, the results first showed an interaction between scale types and CS groups (Table 4), which was hypothesized but not seen TA B L E 5 Mean drop comparisons between the two cognitive style groups (analytic and holistic) for the "too weak" or "too strong" response category with respect to each of the four food samples.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Across the conducted analyses and corresponding results, the consistent finding was a superior performance of the F-AHS, relative to the prior AHS findings from Beekman and Seo (2023; see also Beekman, 2022). This main finding was shown through results from the F-AHS segmentation resulting in greater AH response differences that more closely matched with prior AH literature compared to Beekman and Seo's findings that relied on AHS segmentation (Beekman & Seo, 2023; see also Beekman, 2022) findings that relied on AHS segmentation. When first looking solely at the mean rating differences, the results first showed an interaction between scale types and CS groups (Table 4), which was hypothesized but not seen TA B L E 5 Mean drop comparisons between the two cognitive style groups (analytic and holistic) for the "too weak" or "too strong" response category with respect to each of the four food samples.…”
Section: Discussionsupporting
confidence: 77%
“…The results of this study were then contrasted with the outcomes of Beekman and Seo (2023; see also Beekman, 2022) to compare the results when the AHS or F-AHS were used for CS group segmentation.…”
Section: Data Analysesmentioning
confidence: 99%
“…Much of these cross-cultural comparisons have relied on geographical boundaries to separate cultures, such as analytic and holistic groups, respectively, being associated with Western and Eastern countries. Beekman and Seo [36,110] detailed such analytic-holistic differences, but as their sampling was within an area that would historically be treated as a singular culture (i.e., Northwest Arkansas), these findings speak to the validation of within-cultural analytic-holistic differences found by earlier researchers [32,122]. Such food-related analytic-holistic differences would be replicable in studies investigating more traditional geographically based cultural comparisons, as has been shown repeatedly with the analytic-holistic theory [25].…”
Section: Future Directionsmentioning
confidence: 99%
“…An interesting application here would be employing the analytic-holistic theory to explore its potential mediating impacts on the expansive findings from the Italian Taste project [129]. Consequently, the different areas of the food experience outlined by Beekman and Seo [110], i.e., food shopping, preparing, and consuming, may be impacted differently by individual analytic-holistic constructs. Such a notion is supported by earlier discussion from Miyamoto [38] that detailed how the analytic-holistic theory was developed to be a more general, encompassing theory, and thus such general cognitive tendencies may be modulated in applied scenarios.…”
Section: Future Directionsmentioning
confidence: 99%
“…Aspects of holistic thinking have also been associated with lower susceptibility to the plate size effect, which involves serving and consuming more food when using larger (relative to smaller)sized plates (Sim & Cheon, 2022). Another study by Beekman and Seo (2021) observed that participants who endorsed more holistic thinking styles attend more to the relational aspects of food shopping, preparation and consumption, while those with more analytic thinking styles attended more to the focal elements of these food‐related experiences (e.g., focusing on single ingredients). Yet, it remains unknown whether individual and cultural variation in context‐sensitive tendencies may meaningfully influence evaluations of basic foods characteristics based on the presence of or relationship with other foods.…”
Section: Introductionmentioning
confidence: 99%